Resistance of subarctic soil fungal and invertebrate communities to disruption of below‐ground carbon supply. (17th October 2022) - Parker, Thomas C.; Chomel, Mathilde; Clemmensen, Karina E.; Friggens, Nina L.; Hartley, Iain P.; Johnson, David; Kater, Ilona; Krab, Eveline J.; Lindahl, Björn D.; Street, Lorna E.; Subke, Jens‐Arne; Wookey, Philip A.
Abstract: The supply of recent photosynthate from plants to soils is thought to be a critical mechanism regulating the activity and diversity of soil biota. In the Arctic, large‐scale vegetation transitions are underway in response to warming, and there is an urgent need to understand how these changes affect soil biodiversity and function. We investigated how abundance and diversity of soil fungi and invertebrates responded to a reduction in fresh below‐ground photosynthate supply in treeline birch and willow, achieved using stem girdling. We hypothesised that birch forest would support greater abundance of ectomycorrhizal (ECM) fungal species and fauna than willow shrubs, and that girdling would result in a rapid switch from ECM fungi to saprotrophs as canopy supply of C was cut, with a concomitant decline in soil fauna. Birch forest had greater fungal and faunal abundance with a large contribution of root‐associated ascomycetes (ericoid mycorrhizal fungi and root endophytes) compared to willow shrub plots, which had a higher proportion of saprotrophs and, contrary to our expectations, ECM fungi. Broad‐scale soil fungal and faunal functional group composition was not significantly changed by girdling, even in the third year of treatment. Within the ECM community, there were some changes, with genera that are believed to be particularly C‐demanding declining in girdled plots. However, it was notable how most ECM fungi remained present after 3 years of isolation of the below‐ground compartment from contemporary photosynthate supply. Synthesis . In a treeline/tundra ecosystem, distinct soil communities existed in contrasting vegetation patches within the landscape, but the structure of these communities was resistant to canopy disturbance and concomitant reduction of autotrophic C inputs. Abstract : Soil community composition beneath treeline subarctic trees and shrubs was found to be unchanged in response to severe reduction of carbon delivery to roots and the rhizosphere. Surprisingly, ectomycorrhizal and saprotrophic fungi did not change in abundance, neither did mesofauna. Arctic treeline soil communities, and ecosystems, may be resilient to disturbance events.